2017
DOI: 10.3389/fpsyg.2017.01602
|View full text |Cite
|
Sign up to set email alerts
|

Non-normal Distributions Commonly Used in Health, Education, and Social Sciences: A Systematic Review

Abstract: Statistical analysis is crucial for research and the choice of analytical technique should take into account the specific distribution of data. Although the data obtained from health, educational, and social sciences research are often not normally distributed, there are very few studies detailing which distributions are most likely to represent data in these disciplines. The aim of this systematic review was to determine the frequency of appearance of the most common non-normal distributions in the health, ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 46 publications
1
75
0
3
Order By: Relevance
“…We should mention here that many AI applications [14][15][16][17][18][19][20] are for NGNLEs. For example, most data obtained or measured from health conditions, education, and social sciences are often not normally distributed [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should mention here that many AI applications [14][15][16][17][18][19][20] are for NGNLEs. For example, most data obtained or measured from health conditions, education, and social sciences are often not normally distributed [14].…”
Section: Introductionmentioning
confidence: 99%
“…We should mention here that many AI applications [14][15][16][17][18][19][20] are for NGNLEs. For example, most data obtained or measured from health conditions, education, and social sciences are often not normally distributed [14]. Some examples of non-Gaussian distribution for health conditions, education, and social sciences are prostate cancer modeling [15,16], psychometrics [17], and labor income [18], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, Bono et al [11] found that the most widely used distributions in health, education, and social sciences can be ranked in descending order as follows: gamma, negative binomial, multinomial, binomial, lognormal and exponential.…”
Section: Introductionmentioning
confidence: 99%
“…To this end we conducted a Monte Carlo simulation study to estimate the skewness and kurtosis of the most frequent continuous distributions of the exponential family (gamma, lognormal and exponential), according to Bono et al [11]. The indicators used to assess the bias, precision and accuracy of the different estimators of skewness and kurtosis were, respectively, the relative bias (RB), the coefficient of variation (CV) and the scaled root mean square error (SRMSE).…”
Section: Introductionmentioning
confidence: 99%
“…Distributions of reaction times (RT) and many other quantities in social and life sciences are skewed (asymmetric) (Micceri, 1989;Limpert, Stahel & Abbt, 2001;Bono, Blanca, Arnau & Gómez-Benito, 2017). This asymmetry tends to differ among experimental conditions, such that a measure of central tendency and a measure of spread are insufficient to capture how conditions differ (Balota & Yap, 2011;Trafimow, Wang & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%